The Chronic and Acute Toxicity of Traditional Medicines Containing Terminalia chebula - ARONGQIQIGE; Gerelmaa Enebish; Wang Song; Wei Cheng Xi; Anuujin Gantumur; Oyunbaatar Altanbayar; Hirofumi Shimomura; Battogtokh Chimeddorj; Batnairamdal Chuluun; Avarzed Amgalanbaatar (Korean Pharmacopuncture Institute, 2023)
Objectives: Terminalia chebula, the main ingredient of Altan Arur 5, has been used for many years in traditional medicine. This medicine is more effective than other drugs and is used to treat chronic gastritis and gastrointestinal disorders such as peptic ulcers and esophageal reflux. Other ingredients of Altan Arur 5 are Punica granatum (pomegranate), tulip seeds, black balm, and excreta of Trogopterus xanthipes. The main ingredients of T. chebula are antibacterial and analgesic in traditional medicine. Despite having been used for many years and although many studies have been conducted on the beneficial effects of this medicine and its ingredients, the toxicity of Altan Arur 5 has not yet been elucidated. Therefore, we aimed to study the toxicity of Altan Arur 5 to ensure that it is safe to use.Methods : : Acute and chronic toxicity of Altan Arur 5 were assessed in 10 Kunming mice and 8 Sprague-Dawley rats, respectively, in different doses. In the acute toxicity study, Altan Arur 5 was orally administered to Kunming mice in doses of 12 g/kg, 24 g/kg, and 48 g/kg for 14 days. In the chronic toxicity study, it was orally administered to Sprague-Dawley rats in doses of 1.25 g/kg, 2.5 g/kg, and 5 g/kg for 12 weeks.Results : : No significant differences were observed in the relative organ weights for mice treated with Altan Arur 5 compared with those in the control group. Furthermore, no macro- or microstructural changes were noted in the organs of any group.Conclusion : : Our toxicity testing revealed that the traditional medicine Altan Arur 5 has no toxic effects in vivo. Keywords: traditional